Optimizing mild surface cleaning methods: influence of water purity and pH - Andriani Tsompou; Vitaly Kocherbitov (Scientific Reports)
Abstract Due to growing concerns about the environmental impact of detergents, there has been a notable shift towards researching eco-friendly washing methods, such as using purified water for washing and cleaning. It has been shown that purified water can remove olive oil from hydrophilic surfaces but removing it from hydrophobic surfaces is still a challenge. In this work we studied the removal of olive oil from hydrophobic and hydrophilic surfaces using different water alkalinity, different salt solutions, multiple washing cycles and temperatures. For the hydrophobic surface, gravimetric analysis data demonstrated that non-purified water grades can outperform purified ones, but this effect is due to slight variations of pH. Increasing the pH of purified water by addition of tiny amounts of NaOH (that would not have any environmental impact) significantly enhances cleaning efficiency. For the hydrophilic surfaces, water with increased alkalinity completely removes the oil from the surface in most cases. The study reveals that adjusted pH of otherwise pure water promotes deprotonation of fatty acids in olive oil and facilitates oil removal from surfaces through roll up and interfacial tension reduction mechanisms. Increased temperatures further improve cleaning efficiency. These findings highlight the potential of pH-adjusted purified water as an effective and eco-friendly alternative to conventional cleaning methods. Future research should explore similar techniques on complex materials such as textiles.